Revitalization of Islamic Education: Study on The Existence of Salafiyah Village in Parappe Village, Campalagian Sub-District, Polewali Mandar District - M. Djunaedi (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This article examines traditional education practices, forms of the revitalisation of Islamic education, and efforts at the Salafiyah Parappe Islamic Boarding School to maintain traditional educational practices in facing the opportunities and challenges of modern education. This article departs from qualitative research using an Islamic pedagogic-normative approach. Regarding the revitalisation of Islamic education practised by the Salafiyah Parappe Islamic Boarding School, namely maximising the internal potential of Islamic boarding schools including the development of educators’ competencies, the transformation of methods, media and technology in learning; and strengthening the kiai’s leadership, building boarding school infrastructure. The Salafiyah Parappe Islamic Boarding School’s efforts to maintain traditional educational practices in facing the opportunities and challenges of modern education include revitalising the functions of the people’s demoralisation solution, strengthening the institutional competitiveness of Islamic boarding schools, developing alumni competencies based on needs and social dynamics, strengthening partnerships with related institutions and stakeholders, both the government as well as the private sector, maintaining the independence and independence of Islamic boarding schools, optimising the grounding of the yellow book in the community, expanding the orientation and targets of Islamic boarding schools namely the dimensions of religiosity, social, moral, vocational, and other social community fields.